Adaptive Systems Of Non-Stationary Signals Identification With Additional A-Priory Information; 2015 International Siberian Conference on Control and Communications (SIBCON), Russia, Omsk, May 21−23, 2015 : proceedings - Polishchuk V. I. Vladimir Iosifovich (2015, 2015)
В фонде НТБ ТПУ отсутствует